A study on fractional order thermoelastic half space - Roy, Sourov; Lahiri, Abhijit (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we consider a one dimensional problem on a fractional order generalized thermoelasticity in half space subjected to an instantaneous heat source. The Laplace transform as well as eigen value approach techniques are applied to solve the governing equations of motion and heat conduction. Closed form solutions for displacement, temperature and stress are obtained and presented graphically.
Keywords: thermoelasticity; instantaneous heat source; fractional order; thermoelastic half space; eigen valueapproach